Gemtuzumab ozogamicin for relapsed or primary refractory acute myeloid leukemia in children—the Polish Pediatric Leukemia and Lymphoma Study Group experience - Pawinska-Wasikowska, Katarzyna; Czogala, Malgorzata; Skoczen, Szymon; Surman, Marta; Rygielska, Monika; Ksiazek, Teofila; Pac, Agnieszka; Wieczorek, Aleksandra; Skalska-Sadowska, Jolanta; Samborska, Magdalena; Wachowiak, Jacek; Chaber, Radoslaw; et al. (Frontiers in Immunology, 2023)
Background Gemtuzumab ozogamicin (GO), one of the first targeted drugs used in oncology, consists of an anti-cluster of differentiation 33 (CD33) monoclonal antibody bound to a derivative of cytotoxic calicheamicin. After the drug withdrawn in 2010 due to a significantly higher rate of early deaths, GO regained approval in 2017 for the treatment of newly diagnosed, refractory, or relapsed acute myeloid leukemia (AML) in adults and children over 15 years of age. The objective of the study was a retrospective analysis of clinical characteristics, treatment outcomes, and GO toxicity profile in children with primary refractory or relapsed (R/R) AML treated in Poland from 2008 to 2022. Methods Data were collected through the Polish Registry of Acute Myeloid Leukemia. From January 2008 to December 2022, 35 children with R/R AML were treated with GO in seven centers of the Polish Pediatric Leukemia and Lymphoma Study Group. Results Most of the children (30 of 35) received only one GO cycle in combination with various chemotherapy cycles (IDA-FLA, DOXO-FLA, FLA, FLAG, and others). Eighteen children (51%) achieved complete remission (CR), 14 did not respond to treatment, and three progressed. GO therapy was followed by allogeneic hematopoietic stem cell transplantation (allo-HSCT) in 18 children in CR. The 5-year overall survival (OS) after GO therapy was 37.1% ± 8.7% for the total cohort. There was a trend toward a superior outcome in patients with strong expression of CD33 expression (over 50% positive cells) compared with that in patients with lower expression of CD33 (OS, 41.2% ± 11.9% versus 27.8% ± 13.2%; p = 0.5; 5-year event-free survival, 35.4% ± 11.6% versus 25.7% ± 12.3%; p = 0.5, respectively). Children under 15 years have better outcome (OS, 34.9% ± 10.4% versus 30% ± 14.5%, p = 0.3). The most common adverse events were bone marrow aplasia, fever of unknown origin, infections, and elevated liver enzyme elevation. Sinusoidal obstruction syndrome occurred in two children. Conclusions The use of GO in severely pretreated children, including those under 15 years of age, with previous failure of AML treatment is a feasible and effective bridging therapy to allo-HSCT with an acceptable toxicity profile.